Post-accretionary exhumation of the Meguma terrane relative to the Avalon terrane in the Canadian Appalachians - Archibald, D.; Murphy, J.; Reddy, Steven; Jourdan, Fred; Gillespie, J.; Glorie, S. (Elsevier BV, 2018)
The accretion of the Avalon and Meguma terranes to the Laurentian margin was a major event in the development of the Appalachian orogen. The Minas Fault Zone delineates the boundary between these terranes. A strongly lineated and foliated granite intrusion (Kelly Brook pluton) exposed along the West River St. Mary's Fault intruded into Meguma Supergroup metasedimentary rocks. Well-developed C-S fabrics characterize the pluton with muscovite aligned in the S fabric, and a shallow (~10°) westerly plunging quartz stretching lineation. New U-Pb (zircon, LA-ICP-MS) geochronological data yield a crystallization age of 375.0 ± 4.6 Ma for the Kelly Brook pluton that is indistinguishable from other Late-Devonian intrusive rocks in the Meguma terrane. Petrographic data for muscovite indicate that it grew prior to deformation. A 100% plateau 40Ar/39Ar age of 369.0 ± 1.2 Ma on a single muscovite grain constrains the time of cooling of the granite to approximately 450 to 420 °C. Apatite grains also demonstrate pre- to syn-deformational fabrics and yield a U-Pb (LA-ICP-MS) age of 361.2 ± 5.6 Ma indicating the temperature of the granite was still above 350 °C at this time. Earliest Tournaisian fossils in the unconformably overlying Horton Group strata indicate that the granite was exposed by ca. 359 Ma. Exhumation rates of the Kelly Brook pluton and the Meguma terrane from approximately 9.5–13.3 km depth from ca. 375 Ma to surface exposure at ca. 359 Ma are 0.06 to 0.08 cm yr-1. Estimates for the Upper Devonian regional geothermal gradient in the northern Meguma terrane are high between 39.5 °C km-1 and 67.8 °C km-1, gradients that are common in extensional tectonic environments such as the Basin and Range province. An apatite fission-track age of 215 ± 14 Ma indicates Mesozoic reburial and reheating of the granite prior to opening of the Atlantic Ocean.